Formation Mechanisms of Emotional Intelligence of a Future Psychologist in the Context of Vocational Education - Afanasenko, Larysa A.; Oliinyk, Oksana O.; Tkalych, Marianna H.; Guba, Nataliia O.; Gnevasheva, Vera A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Objective: Emotional intelligence is an indicator of a person’s ability to communicate, the ability to be aware of their emotions and understand the feelings of others. Background: The development of the emotional intelligence of junior university students occurs through various activities, especially in the process of specially organised training and education. This work aims to study the mechanisms of formation of emotional intelligence and stages of formation of emotional intelligence in psychology students. Method: Data analysis, synthesis and pedagogical modelling were used. Scientific works on the formation of emotional intelligence were studied. Results: This paper presents a model of the formation of emotional intelligence in students of psychology and practical recommendations for the formation of emotional intelligence in students. Conclusion: The results obtained in this work can be used in practice during the training of psychological and pedagogical faculties students. Also, the materials presented in this paper can be used by teachers of psychology and pedagogy.